PENGAPLIKASIAN UJI T DALAM PENELITIAN EKSPERIMEN - Azka Dhianti Putri; Ahman Ahman; Rahma Sayyida Hilmia; Salwa Almaliyah; Sidik Permana (LPPM Universitas Bina Bangsa, 2023)
Research is a scientific activity to examine and approve the theory or assumption. In examining assumption, research needs approach and method. Researcher should determine not only the appropriate approach but also the right method to manage finding of research. One of the methods used in quantitative research is T Test. T Test could be used in experimental research design. This study is aimed at exploring the experimental research design by using T Test. This study is a literature review. The result of this study explained the concept of T Test, the concept of experimental research, and the application of T Test in experimental research. The T Test is applied to examine the hypothesis in experimental research